ATTENTION DEFICIT AND HYPERACTIVITY SYMPTOMS IN ADULT PATIENTS WITH TOURETTE SYNDROME. Issue 9 (6th August 2013) - Liew, Ashley; Cavanna, Andrea E
Abstract : Objective: Although attention deficit and hyperactivity disorder (ADHD) is a common co-morbidity in children and young people with Tourette syndrome (TS), little is known about the clinical correlates and impact of ADHD symptoms in adults with TS. We set out to compare tic severity and health-related quality of life (HR-QOL) ratings between adult patients with TS only versus patients with TS plus ADHD. Method: Patients were recruited from the specialist Tourette syndrome clinic at the Department of Neuropsychiatry, Birmingham & Solihull Mental Health Foundation Trust and University of Birmingham. We compared 40 patients with TS only with 32 patients with TS plus ADHD using standardised self-report measures of Adult ADHD (Adult ADHD Severity Scale), tic severity (MOVES) and disease-specific HR-QOL (Gilles de la Tourette Syndrome â€" Quality of Life Scale, GTS-QOL). Results: We found a highly significant difference in tic severity as measured by the MOVES scale, with the TS plus ADHD group reporting higher scores. Likewise, there were highly significant differences in GTS-QOL scores, with the TS plus ADHD group demonstrating worse HR-QOL perception. Finally, the severity of ADHD symptoms showed a significant association with poorer HR-QOL. Conclusion: Adult patients with TS and co-morbid ADHD tend to have higher tic severity and poorer HR-QOL compared to patients with TS only. Clinicians treating adults with TS should screen their patients for residual ADHD symptoms, in order to ensure that appropriate management is provided to prevent potential behavioural difficulties and other functional impairments.